Reassessments of gross domestic product model for fractional derivatives with non-singular and singular kernels - Ozarslan, Ramazan; Bas, Erdal (Springer, 2021)
We study gross domestic product (GDP) model utilizing Atangana-Baleanu, Caputo-Fabrizio and Caputo fractional derivatives under the light of real data of the United Kingdom given by World Bank (World development indicators, 2018) between years 1972-2007. We obtain analytical solutions of fractional models by using Laplace transform. We compare the GDP results obtained for different fractional derivatives with real data by simulations and tables with statistical analysis showing the efficiency of fractional models to the integer-order counterpart employing error sum of squares and residual sum of squares.
Keywords: Gross domestic product; Atangana-Baleanu fractional derivative; Caputo-Fabrizio fractional derivative; Laplace transform; Modeling problem